DEVELOPMENT OF PH-DEPENDENT ANTIBODY FAB VARIANTS THROUGH HISTIDINE SCANNING AND PHAGE DISPLAY: ENHANCED TARGETING OF ACIDIC TUMOR MICROENVIRONMENT - Kinnunen, Anni (My University, 2026)
Cancer immunotherapies function through two main mechanisms; directly, by binding to solid tumors to induce cell death, or indirectly, by enhancing the body’s natural anti-tumor immune response. However, clinical outcomes often vary significantly among patients due to on-target toxicity and immunogenicity, both of which limit treatment efficacy and safety. This thesis aimed to design and engineer pH-dependent antibody Fragment antigen-binding (Fab) variants derived from two clinically approved therapeutic antibodies, Trastuzumab (Herceptin) and Ipilimumab (Yervoy). The pH-sensitive behaviour of these engineered variants enables selective antigen binding, which can be applied to target primarily acidic tumor microenvironment. The aim of pH-dependent binding mechanism is to enhance treatment precision and minimize toxicity in healthy tissues. Engineering was focused on the complementarity-determining regions (CDRs) responsible for antigen binding, by introducing histidine substitutions through a histidine scanning approach using Kunkel mutagenesis. Mutated variants were enriched and selected from the constructed antibody library by phage display. A library of Ipilimumab variable heavy-chain variants was successfully constructed, and histidine-containing variants were enriched through three rounds of selection at pH 6.0. Sanger sequencing revealed novel histidine-mutated sequences, with the most frequent substitutions at Thr33 (45%) in CDR-H1, Asn57 (74 %) and Asp54 (71 %) in CDR-H2, and Pro104 (76 %) in CDR-H3. These findings demonstrate the potential of histidine scanning as a rational strategy for designing pH-dependent antibodies and provide valuable insights for the development of next- generation therapeutic antibodies.
Keywords: on-target toxicity, pH-dependent, Fab, Trastuzumab, Ipilimumab, tumor microenvironment, complementarity-determining region, histidine-scanning, Kunkel mutagenesis, phage display